GE_GERICHTE P/14320/2024 vom 17. Juni 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;VOL(DROIT PÉNAL);AFFILIATION À UNE BANDE;FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;TENTATIVE(DROIT PÉNAL);EXPULSION(DROIT PÉNAL);RÈGLEMENT (CE) 1987/2006;FRAIS JUDICIAIRES;CONSTATATION DES FAITS | CPP.10.al3; CP.139.letb.ch3; CPP.392.al1; CP.47; CP.49; CP.22; CPP.426; NSIS.20; CP.66a.al1.letd